(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article investigates the principles for enhancing the professional competence of future music teachers. It explores the key elements that contribute to the development of music educators’ pedagogical, technical, and personal skills. The research draws from educational theories and current practices in music education, focusing on training programs for future teachers at the university level. Using a mixed-methods approach, data was collected through surveys, interviews with faculty and students, and classroom observations. The findings emphasize the importance of integrating practical training, reflective practice, and collaborative learning in developing the professional competencies of music teacher candidates. The study concludes that a comprehensive, multifaceted approach to teacher education is essential for preparing music educators to meet the diverse needs of their students and the demands of modern music education.